Canine experimental infection - Santos-Gomes, G. M. (2000)
Five mixed breed dogs were inoculated intradermally (ID) with cultured virulent stationary phase promastigotes of Leishmania infantum Nicole, 1908 stocks recently isolated. Parasite transformations in the skin of ID infected dogs were monitored from the moment of inoculation and for 48 h, by skin biopsies. Anti-Leishmania antibody levels were measured by indirect immunofluorescence assay, counterimmunoelectrophoresis and direct agglutination test, and clinical conditions were examined. Thirty minutes after ID inoculation the first amastigotes were visualised and 3 to 4 h after inoculation the promastigotes were phagocytized by neutrophils and by a few macrophages. These cells parasitised by amastigotes progressively disappeared from the skin and 24 h after inoculation parasites were no longer observed. Local granulomes were not observed, however, serological conversion for antibodies anti-Leishmania was achieved in all dogs. Direct agglutination test was the only technique positive in all inoculated dogs. Amastigotes were found in the popliteal lymph node in one dog three months after inoculation. This work demonstrates that, with this inoculum, the promastigotes were transformed into amastigotes and were up taken by neutrophils and macrophages. The surviving parasites may have been disseminated in the canine organism, eliciting a humoral response in all cases.